CRISPR-TSKO: A Tool for Tissue-Specific Genome Editing in Plants. (February 2020) - Ali, Zahir; Mahfouz, Magdy M.; Mansoor, Shahid
Abstract : Functional genomics is at the core of studying the exact function of genes. However, homozygous knockouts of essential and pleiotropic effectors (almost 10% of the genome) are not always possible, thus, functions of these genes remain obscured. The tissue-specific genome editing tool (CRISPR-TSKO) recently described by Decaestecker et al., can characterize these indispensable genes and has wide applications in plants.